Collection and characterisation of Malabar tamarind [Garcinia cambogia (Gaertn.) Desr.] - Z. Abraham S.K. Malik, Gangadhar Eashwar Rao, S. Lakshmi Narayanan and S. Biju (Genetic Resources and Crop Evolution (2006) 53: 401-406, 2006)
A collaborative crop specific exploration and collection mission to collect the germplasm and to study the population size of male and female/hermaphrodite trees of Malabar tamarind [Garcinia cambogia (Gaertn.) Desr.] in the area of its diversity was undertaken during July 2002 in Kerala and Karnataka. A total of 56 accessions of Malabar tamarind were collected. Two collections of Malabar tamarind were found to be very specific because of the uncommon fruit colour, which is pinkish red. All the collected accessions are grown at National Bureau of Plant Genetic Resources (NBPGR) Regional Station, Thrissur for characterisation and conservatin. Extensive range of variability was found in fruit colour, shape, size and nature of branching and canopy of trees. Characterisation of 13 fruit and five seed characters was done for 51 accessions. The variability was found to be maximum for nipple length (74.8 per cent) and minimum for fruit girth (12.8 per cent). Two promising accessions were identified based on mean fruit weight (161 g) in IC 354028 and mean rind thickness (15 mm) and mean rind weight (125 g) in IC 354019.